Ketahanan Pangan Rumah Tangga Petani di Kabupaten Klaten - Wahyu Adhi Saputro; Yuli Fidayani (Jurnal Sosio Agribisnis, 2020)
Food is an important need for humans. Farmers as food producers must also fulfill the food needs of family members in their household. This study aims to determine the level of household food security of farmers in Klaten Regency. Analytical descriptive method is the method used in this study. The research area is in Klaten Regency which was chosen purposively because it is a buffer area and is one of the rice-producing areas in Central Java. The population in this study were farmers in Klaten Regency, while the sample used was 30 farmers in Jambakan Village, which is one of the villages that participated in the independent food village program and Karanglo Village which has an agricultural clinic. The data analysis used was the determination of the level of food security derived from the cross table of Jonsson and Toole. The results showed that most of the farmer households in Klaten Regency were in the food security category.Keywords: food; food security; farmers household